2018
DOI: 10.1590/1678-5150-pvb-5550
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate and nitrite poisoning in sheep and goats caused by ingestion of Portulaca oleracea

Abstract: Three outbreaks of poisoning by Portulaca oleracea were reported in sheep and goats in Northeast Brazil. In the first outbreak, 8 out of 20 sheep were affected and later died. In the second outbreak, three goats and one sheep died out of a flock of 30 animals that included both species. In the third outbreak, two out of 19 sheep were affected, and they recovered after a treatment of 2% methylene blue at a dose of 4 mg/kg body weight. In the first and second outbreaks, the animals ingested P. oleracea after it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…In previous studies in Northeastern Brazil nitrate and nitrite poisoning was associated Pennisetum purpureum and Echinochloa polystachya in cattle (Medeiros et al 2003) and by Portulaca elatior in goats and sheep (Simões et al 2018). In the outbreaks reported herein the disease was caused by P. purpureum and Brachiaria spp, mainly Brachiaria brizantha.…”
Section: Discussionmentioning
confidence: 84%
“…In previous studies in Northeastern Brazil nitrate and nitrite poisoning was associated Pennisetum purpureum and Echinochloa polystachya in cattle (Medeiros et al 2003) and by Portulaca elatior in goats and sheep (Simões et al 2018). In the outbreaks reported herein the disease was caused by P. purpureum and Brachiaria spp, mainly Brachiaria brizantha.…”
Section: Discussionmentioning
confidence: 84%
“…On the other hand, it was found that sheep tolerate the double amount of nitrate administration in the cattle. A study on nitrite poisoning in goats and sheep showed that sheep tolerate up 50% of the nitrate conversion, while death occurs when the nitrate conversion rate exceeds 80% (Simões et al, 2018). Sheep were reported to have more resistance to nitrate toxicity among the ruminants, and their tolerance to the dietary nitrate can be enhanced by acclimation (Alaboudit & Receivedg, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Portulaca oleracea (Portulacaceae) is a plant that usually accumulates nitrates and causes outbreaks of intoxication in the Northeast region of Brazil in pastures invaded by it or when it is cut and administered in feed troughs ( Simões et al, 2018 ). In Chile, poisoning by nitrates and nitrites has been described in cattle by the ingestion of Silybum marianum (Asteraceae) ( Freire and Araya, 1988 ).…”
Section: Poisonous Plants In South Americamentioning
confidence: 99%